Sex‐based differences after a single bout of exercise on PGC1α isoforms in skeletal muscle: A pilot study. Issue 2 (12th January 2021) - D'Amico, Daniela; Marino Gammazza, Antonella; Macaluso, Filippo; Paladino, Letizia; Scalia, Federica; Spinoso, Giulio; Dimauro, Ivan; Caporossi, Daniela; Cappello, Francesco; Di Felice, Valentina; Barone, Rosario
Abstract: To date, there are limited and incomplete data on possible sex‐based differences in fiber‐types of skeletal muscle and their response to physical exercise. Adult healthy male and female mice completed a single bout of endurance exercise to examine the sex‐based differences of the peroxisome proliferator‐activated receptor gamma coactivator 1 alpha (PGC1α), heat shock protein 60 (Hsp60), interleukin 6 (IL‐6) expression, as well as the Myosin Heavy Chain (MHC) fiber‐type distribution in soleus and extensor digitorum longus (EDL) muscles. Our results showed for the first time that in male soleus, a muscle rich of type IIa fibers, endurance exercise activates specifically genes involved in mitochondrial biogenesis such as PGC1 α1 isoform, Hsp60 and IL‐6, whereas the expression of PGC1 α2 and α3 was significantly upregulated in EDL muscle, a fast‐twitch skeletal muscle, independently from the gender. Moreover, we found that the acute response of different PGC1α isoforms was muscle and gender dependent. These findings add a new piece to the huge puzzle of muscle response to physical exercise. Given the importance of these genes in the physiological response of the muscle to exercise, we strongly believe that our data could support future research studies to personalize a specific and sex‐based exercise training protocol.